Defending human rights and the rule of law by the SADC tribunal: Campbell and beyond - Moyo, Admark (University of Cape Town-Juta, 2016)
On 28 November 2008, the Southern African Development Community Tribunal handed down judgment directing Zimbabwe to cease its racially discriminatory land reform programme and to compensate farmers whose land had been compulsorily acquired as a result. Apart from confirming and extending the Tribunal's groundbreaking findings in Mike Campbell (Pvt) Ltd and Others v Republic of Zimbabwe, the article argues that the sorry state of the Tribunal's superficial reasoning on jurisdiction could have been enhanced by considering the approach of other international institutions. Drawing inspiration from international law and the jurisprudence of the South African Constitutional Court, the article argues that racial discrimination cannot solely be established by having regard to the impact of a contested law on a particular racial group. Much depends on the historical context and the fairness of the remedial mechanisms adopted to address prevailing socio-economic disparities between racial groups. The article concludes that the observance of human rights and the rule of law in the region, and the future relevance of the Tribunal, will be determined by the Summit's response to Zimbabwe's disregard of the legal process.